ANALISIS PERSEPSI GURU TERHADAP IMPLEMENTASI KURIKULUM MATEMATIKA BERBASIS PROYEK DI SMP 11 KOTA BENGKULU - Yanti, Yuli; Sumardi, Hari; Muchlis, Effie Efrida; Susanta, Agus (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2026)
This study analyzes mathematics teachers' perceptions of the implementation of a Project-Based Learning curriculum at SMP Negeri 11 in Bengkulu City. The transformation of the learning paradigm from teacher-centered to student-centered through Project-Based Learning (PBL) requires significant adaptation from educators. The study used a descriptive qualitative approach with semi-structured interviews, classroom observations, and documentation analysis with one seventh-grade mathematics teacher. Findings indicate that the school has not provided formal training on Project-Based Learning (PBL), but teachers have participated in independent training through webinars and the MGMP forum. Teachers have positive perceptions of the project-based curriculum implementation because it increases students' learning interest, critical thinking skills, and collaboration skills. Implementation has not been comprehensive across all materials due to limited time, resources, and supporting facilities. The project-based curriculum has a positive impact on student motivation and engagement, although individual participation varies. The study recommends the need for systematic and ongoing training support to optimize the implementation of Project-Based Learning (PBL) in mathematics learning.